Optimization of a thermostable lipase from Bacillus stearothermophilus p1: Overexpression, purification, and characterization - Sinchaikul S. (2014)
An expression library was generated from a partial NcoI and HindIII digest of genomic DNA from the thermophilic bacterium, Bacillus stearothermophilus P1. The DNA fragments were cloned into the expression vector pQE-60 and transformed into Escherichia coli M15[pREP4]. Sequence analysis of a lipase gene showed an open reading frame of 1254 nucleotides coding a 29-amino-acid signal sequence and a mature sequence of 388 amino acids. The expressed lipase was isolated and purified to homogeneity in a single chromatographic step. The molecular mass of the lipase was determined to be approximately 43 kDa by SDS-PAGE and mass spectrometry. The purified lipase had an optimum pH of 8.5 and showed maximal activity at 55°C. It was highly stable in the temperature range of 30-65°C. The highest activity was found with p-nitrophenyl ester-caprate as the synthetic substrate and tricaprylin as the triacylglycerol. Its activity was strongly inhibited by 10 mM phenylmethanesulfonyl fluoride and 1-hexadecanesulfonyl chloride, indicating that it contains a serine residue which plays a key role in the catalytic mechanism. In addition, it was stable for 1 h at 37°C in 0.1% Chaps and Triton X-100. © 2001 Academic Press.